FEMALE’S ISSUES IN CHARACTERIZATION OF INDONESIAN MALAY LITERARY WORKS IN THE ERA from 1920 to 1940 - Abbas (Prosiding Konferensi Internasional Kesusasteraan, 2025)
One of the highlights in Indonesian Malay literary works from 1920 to 1940 is the phenomenon of female’s existence in social and cultural perspectives as reflected in twelve selected novels. This article aims to describe the issues of Indonesian Malay women as reflected in a number of literary works from 1920 to 1940, namely Azab dan Sengsara (1920) by Merari Siregar; Sitti Nurbaya (1922) by Marah Rusli; Salah Asuhan (1928) by Abdoel Moeis; Tak Putus Dirdung Malang (1929) by Sutan Takdir Alisyahbana; Sengsara Brings Nikmat (1929) by Tulis Sutan Sati; Karena Mentua (1930) by Nur Sutan Iskandar; Dian Yang Tak Kunjung Padam (1932) by Sutan Takdir Alisyahbana; Kalau Tak Untung (1933) by Selasih; Si Cebol Rindukan Bulan (1934) by Datuk Madjoido; Hilang Mestika (1934) by Fatimah Hasan Delais or Hamidah; Tenggelamnya Kapal Van Der Wijck (1938) by Hamka; and Layar Terkembang (1938) by Sutan Takdir Alisyahbana. The selected literary works are the main research data analyzed through the integration of the Structural Literary Approach method with Feminist Literary Criticism which emphasizes women’s issues in literary structures such as characterization and themes carried by the literary works. The results of the data analysis are then presented descriptively, namely explaining fictional facts as narrated in literary works. The facts obtained from the narratives of Indonesian Malay literature from 1920 – 1940 related to women’s issues are the intervention of parents and family in matchmaking, devotion to parents, obedience to customs, maintaining purity/self-honor, true love for the soul/spirituality, marriage partners based on social status, death due to failed lovemaking, uneducated women resigned to domestication, and educated women being resilient in facing life’s problems.